Produksi Monogliserida Dengan Esterifikasi Asam Lemak - Fadillatul Nisa; Ida Zahrina; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Monoglyceride (MG) is a compound containing one ester group (-COOR) with a long chain of fatty acids and two hydroxyl groups (-OH). MG is the most widely used compound as an emulsifier in the food industry. Emulsifier is a compound that has surface activity so that it can reduce surface tension and stabilize the emulsion. MG has the ability to reduce surface tension and can stabilize oil and water emulsions. MG can be synthesized through esterification of fatty acids with glycerol using an acid catalyst. Esterification reaction is an endothermal reaction that is reversible and the reaction conditions effect the conversion of the reaction obtained. The operating conditions in the esterification of fatty acids with glycerol effect the reaction conversion as well as the quality of the monoglycerides produced. MG production through esterification of fatty acids with reaction conversion and high purity has been found in the use of DES (deep eutectic solvent) as a catalyst. DES is stable and not volatile so that it can be used repeatedly (reused) without reducing its catalytic activity in the esterification of fatty acids for monoglyceride production. Keywords: DES, emulsifier, esterification, fatty acids, monoglyceride